2010
DOI: 10.1007/s12070-010-0051-3
|View full text |Cite
|
Sign up to set email alerts
|

Otitis Media with Effusion in Children and Its Correlation with Foreign Body in the External Auditory Canal

Abstract: Otitis Media with Effusion (OME) is difined as the chronic accumulation of mucus within the middle ear and sometimes the mastoid air cell system. Significant hearing loss may go unnoticed and may result in improper development of speech and language. Foreign bodies in the external auditory canal of paediatric patients are commonly encountered in day-to-day practice. The purpose was to see if there is any relation between foreign bodies in ears and otitis media with effusion. A prospective study of consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, in studies that were conducted in Croatia (15), in India (29) and in Saudi Arabia (1) reported that males were more affected with OME.…”
Section: Discussionmentioning
confidence: 99%
“…However, in studies that were conducted in Croatia (15), in India (29) and in Saudi Arabia (1) reported that males were more affected with OME.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is meaningful to ask whether the presence of a foreign body in a child's ear simply reflects a meaningless pattern of behavior or whether it may be an indicator of the presence of ear problems. It has been suggested that the presence of an external acoustic meatus foreign body may be a marker for SOM in children (6). Therefore, the purpose of this study was to find out whether a relationship exists between external auditory canal foreign bodies and ear problems.…”
Section: Introductionmentioning
confidence: 95%